Predictors of delayed health seeking for febrile children: multi-level analysis of cross-sectional study data from southern Ethiopia - Chisha, Yilma; Feleke, Tesfaye; Zeleke, Eshetu Andarge; Aschalew, Zeleke; Abate, Zeleke Girma; Haile, Yosef; Dalbo, Mulugeta; Endriyas, Misganu (Frontiers in Public Health, 2024)
Background: Fever is a nonspecific response to various infectious and non-infectious triggers.Febrile illnesses are commonly reported as a primary reason for seeking health care in sub-Saharan Africa. According to WHO, delayed care is a care sought by care providers after 24 hours of fever onset. Timely diagnosis and getting prompt treatment within 24 hours of fever onset is crucial to avert risk of developing severe complications and death due to febrile illness. Understanding factors contributing to delayed health seeking is important for public health interventions. Hence, the aim of this study was Objective: To to assess individual and contextual level factors associated with the delay in seeking prompt treatment for children with fever. in Gamo zone, from September 2022 to June 2023).Method: Community based cross-sectional study was conducted from September 2022 to June 2023 in Gamo zone, Southern Ethiopia. Three districts and from each district, six clusters or Kebele were chosen again by simple random sampling. A total of 820 care givers were randomly selected. A tTwo-level mixed-effects logistic regression model was employed to identify factors associated with the delay in seeking prompt treatment. Associations were measured by adjusted odds ratio and statistical significance was declared at 5% level of significance.The prevalence of delay to in seeking prompt care was 47.8%. Factors contributing for the delay wereare: care givers age 30 years and above (AOR 0.23,: